A reforma da Marinha de Guerra portuguesa no período pombalino (1761/1777): a criação de uma Marinha estritamente militar e profissional e as fontes para seu estudo - Ney Paes Loureiro Malvasio (Navigator)
This work, from the master degree course research, brings up the results about the investments made in the naval construction in the states of Brasil and Grão-Pará during the reign of D. Jose I (1750/1777), focusing in the study of the colonial Arsenais de Marinha (navy shipyards), inaugurated or maintained in this period. The shipyards were located in Belém, Porto Alegre, Rio de Janeiro, Santos e Salvador. The research, however, spread from the results obtained only with the shipyards and bring us the real discovery of the restructuration of the Portuguese navy in the Pombal Era. The work also detail the research books and archive texts available for more studies.